Prognostic significance of spread through air spaces in pulmonary metastases from colorectal cancer. (November 2020) - Takeda-Miyata, Naoko; Konishi, Eiichi; Tanaka, Tadashi; Shimomura, Masanori; Tsunezuka, Hiroaki; Okada, Satoru; Ishihara, Shunta; Ishikawa, Narumi; Inoue, Masayoshi
Highlights: Prognostic impact of STAS in pulmonary metastasis from colorectal cancer is unknown. STAS was related to a poor prognosis in pulmonary metastasis from colorectal cancer. Distance between main tumor and STAS was related to surgical margin relapse. Abstract: Objectives: Surgical resection for pulmonary metastases from colorectal cancer could provide long-term survival in selected patients, and it is commonly performed in practice. However, surgical margin relapse sometimes occurs and is a problematic issue to resolve. Spread through air spaces (STAS) is one of the invasion forms in primary lung cancer and is associated with local recurrence and a poor prognosis. The aim of this study was to evaluate the prognostic significance of STAS for pulmonary metastases from colorectal cancer and to assess the predictability of STAS with preoperative clinical information. Methods: A total of 96 pulmonary metastatic lesions from colorectal cancer in 37 patients who underwent metastasectomy at our institution from January 2008 to December 2013 were retrospectively analyzed. Results: STAS was identified in 41.6 % of the 96 lesions. Surgical margin relapse was found in 8 lesions (8.3 %) from 7 patients (18.9 %). The distance of STAS was identified as an independent risk factor for surgical margin relapse on multivariable analysis ( p = 0.033). The patients with STAS showed significantly worse overall survival than those without (5-year overall survival rate: 30.3 % vs. 76.9 %; p = 0.002). On multivariable analysis, patients with STAS had a significantly higher risk of death than those without ( p = 0.019). An elevated pre-metastasectomy serum carcinoembryonic antigen level was independently correlated with STAS on multivariable analysis ( p = 0.049). Conclusion: STAS was related to a poor prognosis and surgical margin relapse in pulmonary metastases from colorectal cancer.